(untitled) (Sains Humanika, 2014)
Mosque is a religious institution that has an important role in Islamic society. Though the establishment was initially as a place of worship, but the function and its importance is growing from time to time. One of the roles is to develop the Muslims economy through the management of charity, endowment and so on. With the donations and endowment obtained from various parties, mosque institutions are believed to be able to execute this responsibility and trust. Therefore, the purpose of this study is to identify the level ofÂ acceptance of the society towards the mosque the potential of mosque fund expansion in Perak state. This study was conducted on 4,000 respondents across the state of Perak with a total of 2,337 persons (58.42 percent) responded to the questionnaires. The results showed that nearly 75 percent of the respondents agreed that the mosque funds should be expanded to activities that can increase the mosquesâ€™ income and led to a positive impact on society. However, in this effort, a few issues related to the management and administration of mosque must be promptly addressed in order to ensure the role of mosque institution as a center of unity and glory of Muslim society in every aspect of life can be achieved.